Ten Simple Rules for the Care and Feeding of Scientific Data - Goodman, Alyssa; Pepe, Alberto; Blocker, Alexander W.; Borgman, Christine L.; Cranmer, Kyle; Crosas, Merce; Di Stefano, Rosanne; Gil, Yolanda; Groth, Paul; Hedstrom, Margaret; Hogg, David W.; Kashyap, Vinay; et al. (PLoS computational biology, 2014)
Source Code Repositories * Github (http://github.com): A web-based hosting service for software development projects that use the Git revision control system, including many open-source projects. * Git (http://git-scm.com): A free and open-source distributed version control system designed to handle everything from small to very large projects with speed and efficiency. * Mercurial (http://mercurial.selenic.com): A free, distributed source control management tool. Systems to Package, Access, and Execute Data and Code * IPython Notebook (http://ipython.org/notebook.html): A web-based interactive computational environment where you can combine code execution, text, mathematics, plots, and rich media into a single document. * ROpenSci (http://ropensci.org): A suite of packages that allow access to data repositories through the R statistical programming environment. * Authorea (https://authorea.com): A collaborative online word processor for scholarly papers that allows the writing of web-native, living, dynamic, "executable" articles that include text, mathematical notation, images, and data.